Implementation of a real‐time reference and calibration grid platform for improved screening – mapping in Pap test slides. Issue 1 (27th November 2016) - Tsiambas, Evangelos; Riziotis, Christos
Abstract: Cervical cancer screening based on the Papanicolaou (Pap) test is a widely applied but not always efficient practice for detecting Human Papillomavirus (HPV) mediated lesions, partially due to a non‐systematic and inadequate screening process. Our aim was to introduce an inexpensive easy‐to‐use direct screening platform for improved detection of abnormal cells indicative of underlying cervical neoplasia as well as persisting HPV infection. By employing a novel, efficient technique of laser‐based micromachining, we achieved the fabrication of spatial grids on commercially available coverslips allowing visual segmentation of the slide for efficient screening. Abnormal and formerly diagnosed as negative for intraepithelial lesion or malignancy (NILM) Pap test slides ( n = 200) were analyzed by conventional and grid‐based screening. Grid‐based microscopy led to a more reliable diagnosis compared to the conventional by identifying an increased number of abnormal cells ( P = 0.001). It decreased borderline ASCUS, AGC diagnosis, increasing LSIL, HSIL and in situ AdenoCa detection rates closely related with biopsy ( P = 0.015; kappa = 0.978). Concerning the set of NILM diagnoses in rapid re‐screening, the method upgraded six cases ( n = 6) to LSIL ( P = 0.001). The proposed technical solution offers a calibration and orientation visual aid during the on‐site screening process providing significant advantages compared to expensive digital imaging techniques.